A NOTE ON REPORTING RADIOCARBON - Plicht J.V.D.; Hogg A. (My University, 2006)
Recommended reporting practice concerning 14C dates, relevant for Quaternary Geochronology, is given in this report. © 2007 Elsevier Ltd. All rights reserved.
Keywords: 14C; CHRONOLOGY; DATING; RADIOCARBON; Quaternary; Cenozoic::Quaternary; Четвертичный